Autonomous buses: Intentions to use, passenger experiences, and suggestions for improvement. (January 2021) - Mouratidis, Kostas; Cobeña Serrano, Victoria
Highlights: Intention to use autonomous buses was high among study participants. Users were satisfied with the additional departures offered by autonomous buses. Feelings of safety during travel by autonomous bus were generally high. Users' suggestions for improvement focused on higher speeds and softer braking. Autonomous buses seem more applicable for areas with low speeds and low traffic. Abstract: Research on the use of autonomous vehicles as a mode of public transport in a city context is lacking. This paper focuses on the use of recently established autonomous buses (self-driving electric shuttle buses) running along a regular public transport line in a residential area of Oslo, Norway. We use a mixed-methods approach based on survey and interview data from two independent studies. The paper examines intentions to use autonomous buses before and after these were introduced in the case area as well as how passengers experience traveling by autonomous bus. Results show that the intention to use the autonomous buses was mostly positive both before and after using them. Most users felt safe while traveling by autonomous bus. Two suggestions for improvement made by the users were to: increase the speed and reduce the abrupt breaking of the autonomous buses. Overall, outcomes from this paper suggest that residents would be willing to use autonomous buses if these offer more frequent bus departures than the existing ones. However, as full automation has not been achieved yet and there is a host on board who can control the vehicle if necessary, passenger experiences and intentions to use should be reassessed with fully automated buses in future studies.